Fundamental insights into the compressive and flexural response of binder- and aggregate-optimized ultra-high performance concrete (UHPC). (April 2019) - Arora, Aashay; Yao, Yiming; Mobasher, Barzin; Neithalath, Narayanan
Abstract: Ultra-high performance concrete (UHPC) mixtures demonstrating more than 150 MPa compressive strength and 20 MPa flexural strength are proportioned with commonly available cement replacement materials (30% or 50%, mass-based replacement levels) and steel fibers using a recently developed combined binder and aggregate optimization approach. The compressive (axial) stress-strain responses of the unreinforced and fiber-reinforced UHPC mixtures, along with the calculated volumetric strains, are used to define two critical stress states – viz., crack initiation and crack damage stresses. The crack damage stress, being the threshold value at which unstable crack propagation begins, is suggested to be used as the true strength of UHPC in structural design. The influence of matrix composition and fiber volume on these parameters is brought out, to better elucidate the influence of material design on properties. Digital image correlation (DIC) on unnotched beams under flexure is used to show the fundamental differences in the matrix properties that lead to differences in strain localization. The beneficial influence of fibers on strain localization in UHPC mixtures is also brought out.